2021
DOI: 10.1111/1756-185x.14152
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of aqua‐based plyometric exercises in the rehabilitation of patients with juvenile dermatomyositis: A randomized crossover pilot study

Abstract: Background Patients with juvenile dermatomyositis (JDM) experience muscle weakness, tiredness, and loss of energy, which restrict their abilities in performance of their daily living activities. Objective To explore the effect of aquatic‐based plyometric (Aqua‐PLYO) exercises on muscle strength, fatigue, and functional ability in patients with JDM. Methods This was a randomized, single‐blind, crossover pilot study that included 16 patients with JDM (age 13.44 ± 2.85 years). They were assigned randomly to recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 40 publications
1
16
0
Order By: Relevance
“…The significant changes identified in the outcome measures after plyometric exercises are suggested to be due to improving motor activation patterns and co-contraction ratio between both agonist and antagonist muscles, which modified motor control strategies of the upper extremity. This is supported by previous studies that report that plyometric exercises induce and activate higher motor units and reinforce the neural frequency, thereby increasing force production and ameliorates the muscle strength (Elnaggar, 2020;Elnaggar & Abd El-Nabie, 2021).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The significant changes identified in the outcome measures after plyometric exercises are suggested to be due to improving motor activation patterns and co-contraction ratio between both agonist and antagonist muscles, which modified motor control strategies of the upper extremity. This is supported by previous studies that report that plyometric exercises induce and activate higher motor units and reinforce the neural frequency, thereby increasing force production and ameliorates the muscle strength (Elnaggar, 2020;Elnaggar & Abd El-Nabie, 2021).…”
Section: Discussionsupporting
confidence: 82%
“…Therefore, there is a difficulty in comparing the current result with other similar studies. However, several previous studies are available that provide a report on the beneficial effect of the lower extremity plyometric exercises in children with unilateral CP (Elnaggar and Elbanna, 2019; Elnaggar, 2020), juvenile dermatomyositis (Elnaggar & Abd El‐Nabie, 2021), multiple sclerosis (Gürpinar et al., 2020) and healthy individuals (Ploeg et al., 2010). Overall, the reported findings suggested that plyometric exercises conducted for 3‐month have positive effects with significant improvements in muscle power, functional performance and postural stability which nearly backing the results of the present study on the efficacy of plyometric exercises for children with unilateral CP.…”
Section: Discussionmentioning
confidence: 99%
“…Elnaggar et al [ 17 ] evaluated the effects of aquatic plyometric exercises in patients with juvenile DM in a blind randomized trial. The group that performed the exercises showed an improvement in muscle strength (hip flexors and abductors, knee flexors, and extensors), fatigue perception, functionality, and disease activity.…”
Section: Discussionmentioning
confidence: 99%
“…Resistance training in particular, although has not been thoroughly studied in patients with Juv-IA, has been reported as a safe, practicable, and acceptable training approach (as demonstrated by the lack of pain aggravation or any other unfavorable incidents), and may even have positive effects [ 16 , 17 ]. The rationale for the prospective benefits of resistance training for patients with Juv-IA comes from previous research in adults/children with arthritic or other rheumatic conditions [ 10 , 12 , [17] , [18] , [19] ]. Resistance training in adults with rheumatoid arthritis has been shown to enhance strength by a factor of four relative to the baseline, reduce pain by 53%, and improve the 50-foot walking time (all were meaningful compared to controls) [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Resistance training in adults with rheumatoid arthritis has been shown to enhance strength by a factor of four relative to the baseline, reduce pain by 53%, and improve the 50-foot walking time (all were meaningful compared to controls) [ 19 ]. Resistance training has also been proven to be helpful for children with idiopathic arthritis, dermatomyositis, systemic lupus erythematosus, and fibromyalgia [ 10 , 12 , 17 , 18 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%